Peak performance : - Ferrett, Sharon K. (McGraw Hill, 2012)
This new edition includes new features to encourage students to practice their decision making skills and focus on one task at a time to achieve peak performance. This practical guide includes the most “how to” information to give students ample opportunity to put the material into practice.